Differential Toll-like receptor-dependent collagenase expression in chondrocytes. Issue 11 (7th February 2008) - Zhang, Q; Hui, W; Litherland, G J; Barter, M J; Davidson, R; Darrah, C; Donell, S T; Clark, I M; Cawston, T E; Robinson, J H; Rowan, A D; Young, D A
Abstract : Objectives: To characterise the catabolic response of osteoarthritic chondrocytes to Toll-like receptor (TLR) ligands. Methods: Induction of the collagenases, matrix metalloproteinase (MMP)1 and MMP13, by TLR ligands was assessed in chondrocytes by real-time reverse transcriptase (RT)-PCR. TLR signalling pathway activation and their involvement in collagenase induction were confirmed by immunoblotting and use of pathway inhibitors and siRNA. TLR expression was compared in the femoral head cartilage of normal controls and patients with osteoarthritis (OA) by real-time RT-PCR. Results: Ligands for TLR6/2 and TLR3 showed the greatest upregulation of MMP1 and MMP13 respectively, although all TLR ligands upregulated these MMPs. MMP1 and MMP13 induction by TLR3 and TLR1/2 or TLR6/2 ligands were dependent on Trif and MyD88, respectively. These inductions were dependent upon the nuclear factor (NF)κB pathway, but were differentially inhibited by various mitogen-activated protein kinase inhibitors, with MMP13 induction most reliant on the extracellular signal-regulated kinase pathway. In addition, ligands for TLR1/2 and TLR6/2, but not TLR3, induced significant collagenolysis in a cartilage resorption assay. Finally, TLR2 was significantly downregulated and TLR3 upregulated in OA, compared to normal, cartilage. Conclusions: Activation of chondrocyte TLRs leads to differential collagenase gene activation. Treatment of chondrocytes with TLR1/2 or TLR6/2 ligands resulted in collagen resorption. The modulated expression of chondrocyte TLR2 and TLR3 in OA cartilage, compared to normal, may reflect a response to repair cartilage or prevent further extracellular matrix destruction. These data suggest modulation of TLR-mediated signalling as a potential therapeutic strategy for the treatment of OA.